2020
DOI: 10.1002/jbm.a.36957
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin effect on experimental bone defect repair in rat following implantation of the electrospun PLA/carbon nanotubes scaffold associated with Wharton's jelly mesenchymal stem cells

Abstract: In this study, the ability of silymarin to heal rat calvarial bone critical defects with mesenchymal stem cells isolated from human Wharton's jelly (HWJMSC) cultured on the electrospun scaffold of poly (lactic acid)/carbon nanotube (PLA/CNT) has been examined. In this study, 20 adult male Wistar rats were divided into four groups of five each. Under general anesthesia, 8 mm defects were created in the calvarial bone of the rats. Then, study groups were defined as no treatment group, the scaffold alone, the sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In addition, previous studies showed the potential of PLA scaffolds to promote bone regeneration in critical-size models of rats [49][50][51]. Accordingly, we also observed bone formation in the PLA/CHA only group at 3 and 6 months, showing that the scaffold alone is indeed osteoinductive and can be successfully used in bone tissue engineering.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, previous studies showed the potential of PLA scaffolds to promote bone regeneration in critical-size models of rats [49][50][51]. Accordingly, we also observed bone formation in the PLA/CHA only group at 3 and 6 months, showing that the scaffold alone is indeed osteoinductive and can be successfully used in bone tissue engineering.…”
Section: Discussionsupporting
confidence: 73%
“…To instantly improve the availability of cells at the pericranium site, a straightforward approach is the transplantation of autologous cells at the defective sites. Previous in vivo studies have demonstrated that when seeded onto a scaffold, a huge variety of cells, including the endothelial (progenitor) cells forming blood vessels [121,122], and pluripotent mesenchymal stem cells sourced from bone marrow [123,124], fat tissue [125,126], umbilical cord [127,128], dental pulp [129], urine [130], or derived from human induced pluripotent stem cells [131,132], can induce the regeneration of cranium more effectively than cell-free counterparts. Encouraged by these cases, clinical trials were carried out to evaluate the pluripotent stem cells, either sourced from fat [133][134][135] or bone marrow [136], for their capacity to induce the regeneration of the cranium.…”
Section: Enhancing the Osteogenic Potential On The Scalp Sidementioning
confidence: 99%
“…The results show that more new bone formation and mineralization was found in the center and periphery of the bone defect area after filling with icariin-loaded bioactive scaffold, which attribute to the upregulating of osteogenic-related factors, such as RUNX2, ALP, OCN, COLI, BSP and OPN [ 76 , 86 , 91 94 ]. Besides, other TCM combined with different scaffold materials have similar effects, for instance, icaritin [ 88 , 95 ], hydroxy safflower yellow A [ 96 ], kaempferol [ 97 , 98 ], naringin [ 99 , 100 ], quercetin [ 101 103 ], silymarin [ 104 , 105 ], berberine [ 58 , 90 , 106 ], ginsenoside [ 62 , 107 ], resveratrol [ 108 110 ], curcumin [ 111 ], and epigallocatechin gallate [ 112 115 ]. The rat calvarial defect almost completely repaired with physiological integrity at 16 weeks in the PLGA scaffold incorporated with gelatin, alendronate, and naringin groups, and this might owing to the inhibitory impact of alendronate on osteoclasts and the positive effect of naringin on osteoblasts, the PLGA + Gelatin/ALD/NG scaffold had a high potential for bone repair, as shown by upregulating BMP-2, OSX, OPN, BSP, COLI, OCN and calcium content, and inhibiting TRAP [ 116 ].…”
Section: Btementioning
confidence: 99%